A review on the sources, occurrence and health risks of per-/poly-fluoroalkyl substances (PFAS) arising from the manufacture and disposal of electric and electronic products. (December 2020) - Garg, Shafali; Kumar, Pankaj; Mishra, Vandana; Guijt, Rosanne; Singh, Prabhjot; Dumée, Ludovic F.; Sharma, Radhey Shyam
Graphical abstract: Highlights: PFAS pathways from recycling e-products to the environment are described. E-products manufacturing units release PFAS in landfill leachates. E-waste processing sites lead to direct PFAS pollution. PFAS and other e-waste toxicants act synergistically in causing health issues. Critical discussion on the occurrence and remediation routes for PFAS. Abstract: Electric and electronic waste materials (e-waste) serve as a reservoir of highly persistent and extremely toxic inorganic and organic hazardous materials, including per-/poly-fluoroalkyl substances (PFAS) compounds. Besides the electric and electronic industry, PFAS remain an important industrial chemical class because PFAS coating on consumer goods increases their mechanical and thermochemical resistance as well as to tune their liquid repellence properties to oil and water. The release of PFAS from e-waste processing sites and storage landfills into wastewaters was reviewed. It appears that e-waste materials in landfills serve as important nodes for PFAS diffusion to water, soil, hence exerting ecotoxicity on exposed human populations. Evidence from cross-sectional, case-control, and longitudinal studies show that co-occurrence of PFAS and other e-waste toxicants in body fluids and organs of humans act synergistically in causing several health disorders. Based on holistic analyses, the review highlights that PFAS compounds significantly contribute to e-waste pollution, which needs immediate attention from policymakers.